A novel molecular imprint polymer quartz crystal microbalance nanosensor for the detection of andrographolide in the medicinal plant extract - Shafiqul Islam, A. K. M.; Krishnan, Hemavathi; Ahmad, Mohd Noor; Nadaraja, Pubalan; Helal Uddin, A.B.M. (Pleiades Publishing, 2020)
A novel quartz crystal microbalance (QCM) sensor based on molecular imprint polymer (MIP) has been developed for the detection of andrographolide in the medicinal plant extracts. The MIP and non- imprinted polymer (NIP) were synthesized using a precipitation polymerization method. The polymers were characterized by Fourier-transform infrared spectrometry (FTIR), scanning electron microscopy (SEM) and cyclic voltammetry. Both MIP and NIP were deposited on quartz crystal platform using an electro-polymerization method. A linear Langmuir isotherm model revealed that the MIP-QCM sensor has the maximum binding sites 18.02 ng cm–2. It was found that 92.8% of andrographolide was detected in 0.10 μ g mL–1 of plant extract, and the limits of detection and quantification values were 1.21 ng cm–2 and 4.02 ng cm–2, respectively. This research showed that the andrographolide imprinted polymer could be used to detect and quantify andrographolide in Andrographis paniculata plant extract in both analytical separation and sensor development.